Utilization of Canva Application for Maharah Learning - Raisha Fasya; Cheen May; Deguchi Adelir; Qyoki Delr (Lingeduca: Journal of Language and Education Studies, 2022)
The selection of one of the learning media is a point that greatly affects the effectiveness of learning in an educational institution. Selection of one of the learning support tools in an educational institution. This statement, it turns out, has not achieved the education that the school community dreams of. however, a teacher and several agencies must think of appropriate efforts so that this kind of problem can be solved. For a student, it aims to be used in the learning process in a class later. So that from there it is also easier for students to store again and absorb again the material that will be posted by the educator. The purpose of this research is to further develop internet - based audio - visual - based learning media. The observation prefers how to approach the object of research and identify learning materials, then analyze and then identify the location of the study, the suitability between the content, the presence of mendisen, and the comparison of mendisen. internet-based through sound in the form of Canva media to critique sound recordings with tracks in order to attract the attention of students so as to create the desired education. Thus, the learning media that we develop can be used in the learning process or from daring to attract.